PERBANDINGAN TINGKAT KEUNTUNGAN DAN PEMASARAN UNIT PEMBENIHAN RAKYAT IKAN LELE (Clarias sp.) PADA UPR KELOMPOK DAN UPR SWADAYA DI KOTA PALEMBANG (JASEP, 2020)
This research is purpose to (1) calculate the profit rate of hatchery’s group and individual hatchery in Palembang (2) calculate the marketing efficiency of baby catfish which consider to marketing channels, marketing margins, marketing cost and farmer’s share at hatchery’s group and individual hatchery in Palembang (3) comparison the management system of hatchery’s group and individual hatchery also related with the profit rate and marketing baby catfish in Palembang. The results of this research are indicate that the profit rate earned by hatchery’s group was 4.20 percent higher than individual hatchery was only received amounted to 3.43 percent. The marketing efficiency rate of baby catfish in hatchery’s group is more efficient than the individual hatchery seen from the aspect of marketing channels, marketing costs, marketing margins, and the farmer's share. The management system of hatchery’s group better than individual hatchery, in hatchery’s group marketing channels have been set up so that the sale price of baby catfish is equal among group members. Hatchery’s group made production schedule arrangements between members of the group so that the supply of baby catfish is always available.